Rigor and Dilemmas in The Statutory Audit Mission in The Context of The Health Crisis - Marioara MOLOCINIUC (HRITCAN) (Communications of International Proceedings, 2021)
In the era of continuous ascension in which we find ourselves, the role of statutory audit has increased turning into a strategic pillar in economic development. In such circumstances, in which multinational companies face numerous situations of risk and uncertainty, looking for solutions in risk management and business recovery, the work of auditors is increasingly in the sight of shareholders, regulators and the public. Statutory auditors must receive and actively respond to market challenges. Therefore, the impact of the pandemic is significant, highlighting the drivers to accept the audit mission, as well as the identification of threats, dilemmas to the fundamental principles of ethics, contribute decisively to improving the effectiveness and efficiency of audit missions.
Keywords: statutory audit; ethics; morality; ethical dilemmas; threats.